Four-Dimensional CT Analysis of Dorsal Intercalated Segment Instability in patients with Suspected Scapholunate Instability - Athlani, Lionel; Granero, Jonathan; Rouizi, Kamel; Hossu, Gabriela; Blum, Alain; Dautel, Gilles; Gondim Teixeira, Pedro Augusto (Journal of Wrist Surgery, 2021)
Background In this study we sought to evaluate the contribution of dynamic four-dimensional computed tomography (4DCT) relative to the standard imaging work-up for the identification of the dorsal intercalated segment instability (DISI) in patients with suspected chronic scapholunate instability (SLI).Methods Forty patients (22 men, 18 women; mean age 46.5 ± 13.1 years) with suspected SLI were evaluated prospectively with radiographs, arthrography, and 4DCT. Based on radiographs and CT arthrography, three groups were defined: positive SLI (n = 16), negative SLI (n = 19), and questionable SLI (n = 5). Two independent readers used 4DCT to evaluate the lunocapitate angle (LCA) (mean, max, coefficient of variation [CV], and range values) during radioulnar deviation.Results The interobserver variability of the 4DCT variables was deemed excellent (intraclass correlation coefficient = 0.79 to 0.96). Between the three groups, there was no identifiable difference for the LCAmean. The LCAmax values were lower in the positive SLI group (88 degrees) than the negative SLI group (102 degrees). The positive SLI group had significantly lower LCAcv (7% vs. 12%, p = 0.02) and LCArange (18 vs. 27 degrees, p = 0.01) values than the negative SLI group. The difference in all the LCA parameters between the positive SLI group and the questionable SLI group was not statistically significant. When comparing the negative SLI and questionable SLI groups, the LCAcv (p = 0.03) and LCArange (p = 0.02) values were also significantly different. The best differentiation between patients with and without SLI was obtained with a LCAcv and LCArange threshold values of 9% (specificity of 63% and sensitivity of 62%) and 20 degrees (specificity of 71% and sensitivity of 63%), respectively.Conclusion In this study, 4DCT appeared as a quantitative and reproducible relevant tool for the evaluation of DISI deformity in cases of SLI, including for patients presenting with questionable initial radiography findings.Level of evidence This is a Level III study.
Keywords: carpal instability; dorsal intercalated segment instability; four-dimensional computed tomography; kinematics; scapholunate ligament